2018
DOI: 10.1002/jpen.1489
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Psyllium Fiber Supplementation on Diarrhea Incidence in Enteral Tube‐Fed Patients: A Prospective, Randomized, and Controlled Trial

Abstract: Background Diarrhea in enteral tube‐fed patients is not uncommon and can lead to unfavorable outcomes. Fiber in enteral nutrition (EN) formula might play a role in postfeeding diarrhea. Theoretically, soluble fiber is beneficial for both prevention and treatment of postfeeding diarrhea, but different types of soluble fiber may not provide the same effect. This study aims to determine whether supplementation with psyllium in standard EN reduces the incidence of diarrhea in tube‐fed patients. Methods We conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 45 publications
1
10
0
Order By: Relevance
“…We used the King's stool chart, 13 which was developed specifically to evaluate fecal output in patients receiving enteral tube feeding, instead of using the more generalized definition of >3 bowel movements per day, considering that hospitalized patients receiving EN are often in diapers, which makes an assessment of bowel movement frequency difficult and perhaps even invalid. In our study, the excellent agreement among the nursing staff was observed with an intra‐class correlation coefficient of 0.878 after the King's stool chart training 12 . Diarrhea was defined as a King's stool score ≥15.…”
Section: Methodssupporting
confidence: 54%
See 3 more Smart Citations
“…We used the King's stool chart, 13 which was developed specifically to evaluate fecal output in patients receiving enteral tube feeding, instead of using the more generalized definition of >3 bowel movements per day, considering that hospitalized patients receiving EN are often in diapers, which makes an assessment of bowel movement frequency difficult and perhaps even invalid. In our study, the excellent agreement among the nursing staff was observed with an intra‐class correlation coefficient of 0.878 after the King's stool chart training 12 . Diarrhea was defined as a King's stool score ≥15.…”
Section: Methodssupporting
confidence: 54%
“…As mentioned earlier, we used the King's stool chart, 13 which was specifically developed to assess fecal output in patients on EN in this study, instead of using the more generalized definition of >3 bowel movements per day. The King's stool chart has been validated in tube‐fed patients and showed concurrent validity and inter‐rater reliability, 13,16–18 including in our RCT, as an excellent agreement was observed with an intra‐class correlation coefficient of 0.878 12 . In the present study, post‐feeding diarrhea occurred in 37.1% of hospitalized patients in general medical wards, which is similar to the 39–41% from other studies in the same setting of general medical patients on EN feeding 15,19 …”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Some authors suggest a dose of 18-30 g/day of P. psyllium to normalise the stools in patients with chronic diarrhoea, suggesting a gradually increasing dose to improve tolerance [55]. More recently, Lertpipopmetha et al reported no beneficial effect on reducing incidence of diarrhoea in general medical patients (43% with infectious diseases) receiving enteral nutrition enriched with 15.2 g/l of psyllium fibre [56].…”
Section: Fibre and Prebioticsmentioning
confidence: 99%